2018
DOI: 10.1002/2211-5463.12461
|View full text |Cite
|
Sign up to set email alerts
|

Acidic mammalian chitinase gene is highly expressed in the special oxyntic glands of Manis javanica

Abstract: The Malayan pangolin ( Manis javanica ) is a mammal that feeds primarily on ants and termites, which contain the energy‐rich carbohydrate chitin. Chitin is digestible by endogenous enzymes of the typical mammalian gastrointestinal tract, especially the acidic mammalian chitinase ( AMC ase). The objective of this research was to determine whether AMC ase activity is expressed in the stomach of M. javanica . The stomach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Moreover, compared to those of carnivores, pangolins have longer intestinal tracts, 24 which may allow chitinase more time for chitin digestion in the intestine. Together with the chitinase expressed in its saliva and stomach, 27 these constitute an adaptation that allows the utilization of ants and termites as primary food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared to those of carnivores, pangolins have longer intestinal tracts, 24 which may allow chitinase more time for chitin digestion in the intestine. Together with the chitinase expressed in its saliva and stomach, 27 these constitute an adaptation that allows the utilization of ants and termites as primary food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Acidic chitinase (Chia; also referred to acidic mammalian chitinase, “AMCase”; Boot et al 2001 , 2005 ) hydrolyzes the β-1, 4 glycoside bonds of chitin, a major structural polysaccharide in insects ( Bueter et al 2013 ; Wysokowski et al 2015 ; Van Dyken and Locksley 2018 ). Chia is expressed in the stomachs of insectivorous and omnivorous animals including bat ( Strobel et al 2013 ), mouse ( Ohno et al 2016 ), pangolin ( Ma et al 2018 ), crab-eating monkey ( Uehara et al 2018 , 2021 ), and common marmoset ( Tabata, Kashimura, et al 2019 ). In addition, omnivorous livestock animals, such as chicken and pig, express Chia at high levels in their stomachs and are able to degrade chitin and chitin-containing materials such as shrimp shells and mealworm larvae shells under normal gastrointestinal conditions ( Tabata, Kashimura, Wakita, Ohno, Sakaguchi, Sugahara, Imamura, et al 2017 ; Tabata, Kashimura, Wakita, Ohno, Sakaguchi, Sugahara, Kino, et al 2017 ; Tabata, Kashimura, Wakita, et al 2018 ; Tabata, Wakita, et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various Chia has been reported in mammals and birds, while mouse Chia has been studied the most extensively so far [8,[21][22][23][24]52]. Recently, Du et al reported an increased yield of (GlcNAc) 2 by recombinant mouse Chia produced in Pichia pastris using industrial and agricultural applications [53].…”
Section: Discussionmentioning
confidence: 99%